Stress Inducible Overexpression of AtHDG11 Leads to Improved Drought and Salt Stress Tolerance in Peanut (Arachis hypogaea L.) - Banavath, Jayanna N.; Chakradhar, Thammineni; Pandit, Varakumar; Konduru, Sravani; Guduru, Krishna K.; Akila, Chandra S.; Podha, Sudhakar; Puli, Chandra O. R. (Frontiers in Chemistry, 2018)
Peanut is an important oilseed and food legume cultivated as a rain-fed crop in semi-arid tropics. Drought and high salinity are the major abiotic stresses limiting the peanut productivity in this region. Development of drought and salt tolerant peanut varieties with improved yield potential using biotechnological approach is highly desirable to improve the peanut productivity in marginal geographies. As abiotic stress tolerance and yield represent complex traits, engineering of regulatory genes to produce abiotic stress-resilient transgenic crops appears to be a viable approach. In the present study, we developed transgenic peanut plants expressing an Arabidopsis homeodomain-leucine zipper transcription factor (AtHDG11) under stress inducible rd29Apromoter. A stress-inducible expression of AtHDG11 in three independent homozygous transgenic peanut lines resulted in improved drought and salt tolerance through up-regulation of known stress responsive genes(LEA, HSP70, Cu/Zn SOD, APX, P5CS, NCED1, RRS5, ERF1, NAC4, MIPS, Aquaporin, TIP, ELIP ) in the stress gene network , antioxidative enzymes, free proline along with improved water use efficiency traits such as longer root system, reduced stomatal density, higher chlorophyll content, increased specific leaf area, improved photosynthetic rates and increased intrinsic instantaneous WUE. Transgenic peanut plants displayed high yield compared to non-transgenic plants under both drought and salt stress conditions. Holistically, our study demonstrates the potentiality of stress-induced expression of AtHDG11 to improve the drought, salt tolerance in peanut.